Tax options and the pricing of treasury bond triplets - Jordan, Bradford D.; Jordan, Susan D. (Journal of Financial Economics, 1991)
This study uses Treasury bond triplets, which consist of three different Treasury issues with a common maturity date, to investigate the theoretical and empirical influence of tax strategies on Treasury prices. The tax-option effect, which arises from the right to optimally realize gains and losses for tax purposes, is found to induce convexity in the relation among triplet bond prices, but the effect is too small to create an arbitrage opportunity. A previous study [Litzenberger and Rolfo (1984)] is shown to incorrectly isolate the tax-option effect and hence misstate some key result; a correction is provided.